Multifunctional coreid bug pheromones for efficient bioprotection against legume pests and enhanced food productivity - Kpongbe, H.; Khamis, F.; Cheseto, X.; Kirwa, H.; Tamò, Manuele; Torto, B. (2024)
In Africa, food legumes such as cowpeas and beans constitute important sources of proteins for millions of rural and urban populations. However, attacks by multiple pest species can reduce yields by up to 80%. Small-holder farmers protect their crops against pests using conventional insecticides, thereby contributing to insecticide resistance and jeopardizing food safety. To date, no alternative sustainable practices are available to reduce insecticide use in the management of legume pests. This study aimed to provide a sustainable alternative to insecticide use based on semiochemicals to manage multiple legume pest species and enhance food productivity.